2016
DOI: 10.7314/apjcp.2016.17.2.767
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based Population of Elderly Cancer Cases in Northeastern Thailand

Abstract: Background: The proportion of aged Thais (≥65 years old) is expected to be 30% by 2030, leading to an increased number of elderly cancer cases. Older individuals have distinct patterns of cancer and treatment needs. We therefore conducted the present study of new cancer cases and trends to get a perspective on the elderly cancer situation in Northeast Thailand. Materials and Methods: All new elderly cancer cases (≥65 years) registered in the hospital-based cancer registry at the Faculty of Medicine, Srinagarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In our cohort, we found that advanced age was correlated with decreased lean muscle mass, for each 1-year age increase, appendicular muscle mass decreased 0.10 kg. Since the incidence of elderly cancer is increasing [ 23 , 24 ], evaluation of muscle mass along with geriatric assessment in elderly patients receiving chemotherapy is warranted. Female gender was also a risk for decreased muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, we found that advanced age was correlated with decreased lean muscle mass, for each 1-year age increase, appendicular muscle mass decreased 0.10 kg. Since the incidence of elderly cancer is increasing [ 23 , 24 ], evaluation of muscle mass along with geriatric assessment in elderly patients receiving chemotherapy is warranted. Female gender was also a risk for decreased muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…e incidence of elderly cancer is also increasing since aging is one of the important risk factors for cancer. Between 1993 and 2012, the proportion of elderly cancer increased from 30 percent to 46 percent from the first to second decade [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many countries are facing an aging society as the proportion of people aged over 65 years is growing tremendously 1. The number of elderly cancer patients has also been growing simultaneously 2…”
Section: Introductionmentioning
confidence: 99%